TAQNet: Traffic-Aware Minimum-Cost Quantum Communication Network Planning - Ilora Maity; Junaid ur Rehman; Symeon Chatzinotas (IEEE Transactions on Quantum Engineering)
Quantum key distribution (QKD) provides a secure method to exchange encrypted information between two parties in a quantum communication infrastructure (QCI). The primary challenge in deploying a QCI is the cost of using optical fibers and trusted repeater nodes (TRNs). Practical systems combine quantum and classical channels on the same fiber to reduce the cost of fibers dedicated to QKD. In such a system with quantum-classical coexistence, the optimal distribution of QKD requests with minimal deployment cost and power usage on the multiplexed links is challenging due to the diverse key rate demands of the requests, number of classical and quantum channels, guard band spacing between classical and quantum channels, and secret key rate of the quantum channels that decreases with distance. To address these challenges, in this work, we propose a Steiner tree-based approach for constructing a QCI that connects all quantum nodes with minimum TRNs. In addition, we propose a genetic algorithm-based solution to optimally distribute the end-to-end QKD requests over the QCI. We also determine feasible optical bypass routes to reduce the overall energy consumption in the network further. The proposed approach reduces the QCI deployment cost by 19.42% compared to the benchmark MST-Baseline. Also, on average, TAQNet with optical bypass achieves 4.69 kbit per Joule more energy efficiency compared to the nonbypass approach.